Characterization of Laser Structuring on AISI 304 Stainless Steel - Edan, Sarah Sabah; Taha, Rana M. (Al-Nahrain Journal for Engineering Sciences, 2025)
Super-hydrophobic is the tendency of a surface to spit out water droplets. Only a surface with high apparent contact angle (>1500), low contact angle hysteresis (